IMPLEMENTATION OF GRATITUDE IN PROSOCIAL BEHAVIOR: (RESEARCH ON FPRB VOLUNTEERS JOMBANG REGENCY) - Imam Subakti; Dyan Evita Santi (International Conference on Humanity Education and Society (ICHES), 2023)
Disasters often occur in disaster-prone areas so that policy makers seek solutions by forming a community organization to deal with the impact of natural disasters, disasters can be minimized in various ways to reduce disaster risk by inviting people who have prosocial behavior including volunteers to participate in independent organizations such as The Disaster Risk Reduction Forum, which in its duties always instills a sense of gratitude for volunteers to have high prosocial behavior,This qualitative research aims to find out how gratitude can be implemented in prosocial behavior by observing and interviewing 4 (four) respondents/volunteers taken randomly from 40 (forty) volunteers who took part in the training program Disaster Risk Reduction in Bugasur Kedaleman Village, Gudo District, Jombang Regency. The results of this study describe that someone who is grateful has good control over his environment, is able to face life's difficulties, behaves prosocially, seeks social support from others, interprets experiences from different perspectives, and has a plan in solving problems.